Determinación del efecto de cepas nativas de Trichoderma spp., en el desarrollo del sistema radical en el cultivo de palma aceitera (Elaeis guineensis Jacq) en la zona de La Unión - Quinindé. - Martínez Cadena, Miguel Ángel (2012)
Currently, one of the main problems in the cultivation of oil palm (Elaeis guineensis Jacq.) it is poor radical development, due to the poor agronomic management, mainly in what refers to fertilization and growth stimulation, added to this is the substantial loss of the microbiological quality of the soil, which affects the plant-microbe relationship. In the present research it was studied the effect of several native strains of Trichoderma sp., in the development of the root system in the cultivation of palm oil. Four (4) native strains of Trichoderma sp., were evaluated in laboratory, noting radial growth. The best three strains were inoculated in 8 oil palm plants placing 15 grams at the beginning, the third and the fifth month of the experimental trial. Assessments were developed for 190 days after application. In the laboratory, in the first and second day presented the greatest radial growth treatment 1 (Trichoderma spp SL 1 + rachis ) with an average of 1.5 to 3.7 mm, and the third day presented an average of 4, 4 stop the treatment 1 (Trichoderma spp Spine SL 1 + rachis ), 2 (Trichoderma spp SL 2 + rachis ), 3 (Trichoderma spp C + rachis) The treatment with more fresh weight of root was T2 (Trichoderma spp. + rachis) with average of 127.1 grams in the initial assessment and the second treatment 1 (Trichoderma spp S.L 1 + rachis) with average of 214.8 grams. In terms of dry weight during the first data registration the T2 (Trichoderma spp S.L 2 + rachis) greatest with an average of 70.10 grams. The second treatment showed the greatest weight was T1 (Trichoderma spp S.L 1 + rachis) with on average of 103.23 grams For the variable length of root, during in the first data segistrative, the treatment with greater length of root was the T5 (Plants + rachis) with on average of 53.18 cm. In the second evaluation was T1 (Trichoderma spp S.L 1 + Rachis) with an average of 100.36 centimeters